Predicting corporate financial distress using logistic regression : Malaysian evidence / Tew You Hoo and Enylina Nordin - Tew, You Hoo; Nordin, Enylina (Institute of Research, Development and Commercialization (IRDC), 2006)
This study attempts to construct and test financial distress prediction model for Malaysian Companies. The samplefor this study consists of84 companies listed on Bursa Malaysia that became financially distressed in 200/ and 2002 and a matched (by industry and firm size) sample 0/ 84 financially healthy companies. The model is constructed by employing logistic regression analysis based on pooled data of5 years prior tofinancial distress. The model isfirst derived using the estimation sample andthen tested using the validation sample. Adding to the existing research onfinancial distress prediction models, the current model utilizes measures ofshareholders' equity to total liabilities, shareholders' equity to total assets, current liabilities to total assets, total borrowings to total assets andinventory turnover. The results are encouraging, as the model developed/or predicting corporatefinancial distress in Malaysia is reliable up to 5 years prior to financial distress. II is also believed thai the prediction model can be useful to different groups of users such as policy makers, financial institutions, creditors, managers, bankers, investors and shareholders.